Theorizing Teaching Current Status and Open Issues - Praetorius, Anna-Katharina; Charalambous, Charalambos Y. (Springer Nature, 2023)
This open access book seeks to create a forum for discussing key questions regarding theories on teaching: Which theories of teaching do we have? What are their attributes? What do they contain? How are they generated? How context-sensitive and content-specific do they need to be? Is it possible or even desirable to develop a comprehensive theory of teaching? The book identifies areas of convergence and divergence among the answers to these questions by prominent international scholars in research on teaching. Initiating exchanges among the authors, it then evaluates whether consensus can be reached on the areas of divergence. The book concludes by discussing lessons learned from this endeavor and outlines steps that need to be taken for advancing future work on theorizing teaching. As such, the book is aimed at readers interested in an overview of the theorizing of teaching and key open questions that, if addressed, help to move the field forward.